Studying Engineering Characteristics of Asphalt Binder and Mixture Modified by Nanosilica and Estimating Their Correlations - Moein Hasaninia; Farshad Haddadi (Advances in Materials Science and Engineering)
The objective of this research was to investigate rutting and fatigue distresses in asphalt containing 2, 4, 6, and 8 percent of nanosilica (NC) and to find out the correlation between engineering properties of the modified binder and mixture asphalt. In order to study the effect of NC on the rutting and fatigue properties of modified binders, the multiple stress creep recovery (MSCR) and linear amplitude sweep (LAS) tests were carried out. The Marshall stability, dynamic creep, and four-point bending beam fatigue tests were used to evaluate performance characteristics of the mixtures. The binder and mixture tests all indicated an improvement of fatigue and rutting resistance using NC as a modifier. Furthermore, some statistical correlations between engineering properties were developed successfully.